Economic Development and Allocation in Family Farmers in Indonesia - Ashari Ashari (Journal of Social Science and Economics (JOSSE), 2026)
This research, which is significant, examines the relationship between development and economic allocation within farming families in Indonesia. The study focuses on the impact of development on the socio-economic dynamics of farming families. Development is characterized by agricultural mechanization, expanded employment opportunities, and advanced education, which stimulate the lifestyles of farming families. However, these changes still leave a number of problems within farming families, including economic inequality. This research uses a literature review method, drawing on a number of sources (books, articles, freelance writing, and research results) related to the research objectives. The results of the study indicate that development has dynamized changes in the rural economy, particularly the participation of women in both agricultural and non-agricultural sectors. Development has had a real impact through the role of farmers (including women) in improving and strengthening the family economy. However, the economic allocation of farming families in Indonesia is still linked to patriarchal traditions that construct men as having the maximum allocation of power within the family. This is a real problem and represents an inequality in the development of farming family communities in Indonesia. However, development has shown an increase in farmers' welfare in several areas of life.